New techniques for multiple wavelength fiber laser generation based on edfa and tdfa - Ahmad, Nurul ‘Atiqah (2019)
Multiple wavelength fiber laser (MWFL) can be a potential source for microwave generation as the conventional microwave generator have several issues in generating high frequency. In order to be such source, the MWFL must have the following criterion; a great number of comb lines, a compact design, adjustable and switchable wavelength spacing, as well as stable MWFL. Four main research studies are successfully demonstrated in efforts to improve the performance of MWFL either based on erbium doped fiber amplifier (EDFA) or thulium doped fiber amplifier (TDFA). The first study is related to a numerical analysis of Brillouin erbium fiber laser (BEFL). In this study, the elements of EDFA and stimulated Brillouin scattering (SBS) effect are thoroughly investigated. It is found that the optimum length of erbium doped fiber (EDF) is 10 m and the residual waves exist in the forward propagation. These findings successfully generate up to 10 Stokes lines. The second research work is related to an experimental study on the four-wave mixing cascades (FWMC) seeded by a BEFL. In the experiment, the Brillouin pump (BP) wavelength is varied to optimize the number of comb lines. Experimental results show that up to 80 comb lines is generated when the BP wavelength is varied at 1560 nm. In the third research work, an experimental setup of dual-wavelength Brillouin thulium fiber laser (BTFL) with an adjustable Brillouin frequency spacing (BFS) is designed. The proposed design incorporates a micro air gap in the BTFL cavity. This study successfully generates dual wavelength with single-, double-, and triple- BFS which has wavelength spacing of 0.084 nm, 0.166 nm, and 0.254 nm, respectively. The fourth research work is associated with the generation of multiple wavelength thulium-doped fiber laser (TDFL) by splicing single mode fiber (SMF) at both ends of 2.5 m two-mode step index fiber (TMSIF). The proposed scheme successfully generates up to 8 stable laser lines with wavelength spacing of 0.8 nm. Based on the experimental results of BTFL and TDFL, the proposed scheme is able to generate a microwave signals for 10 GHz, 20 GHz, 30 GHz, and 100 GHz region, respectively.